2017
DOI: 10.3141/2636-05
|View full text |Cite
|
Sign up to set email alerts
|

Safety Performance of Flashing Yellow Arrow for Protected–Permissive Left-Turn Signal Control in Central Illinois

Abstract: In 2010, the Illinois Department of Transportation began implementing the flashing yellow arrow (FYA) at intersections operating with protected–permissive left-turn (PPLT) control. Research was conducted to evaluate the safety-effectiveness of FYAs at 86 intersections and 164 approaches in central Illinois. The effectiveness evaluation was performed with 3 years of before-and-after FYA installation crash data and the empirical Bayes method. In the before condition, the left-turn signals operated with a circula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Two sets of results were reported for each category-the ''first set'' only included intersections that were exclusive to that category, and the ''second set'' included all legs that belonged to that category. The categories along with the CMFs are provided below: (6). The evaluation included 86 intersections where the state had implemented FYA on 164 approaches.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Two sets of results were reported for each category-the ''first set'' only included intersections that were exclusive to that category, and the ''second set'' included all legs that belonged to that category. The categories along with the CMFs are provided below: (6). The evaluation included 86 intersections where the state had implemented FYA on 164 approaches.…”
Section: Literature Reviewmentioning
confidence: 99%
“…More recently, supplementary signage was evaluated in parallel to FYA installation in a four-and fivesection signal. In this study by Schattler et al, the results found that supplemental signage has a need in assisting driver comprehension with the FYA indication (13). Research continues to prosper in this area as safety impacts of the implementation of the FYA continue to emerge.…”
Section: Effects Of Fya Driver Comprehension and Supplementary Signagementioning
confidence: 82%
“…Rietgraf et al found that there was no significant difference in having areas with one permissive indication for left-turns compared to areas with multiple permissive left-turn indications; however, that evidence suggests consistency in permissive indications may yield a stronger comprehension rate (11). In addition to this, researchers continue to focus on the comprehension of supplementary signage with the FYA left-turn indication (12), (13).…”
Section: Effects Of Fya Driver Comprehension and Supplementary Signagementioning
confidence: 99%
“…A study of a site in Austin, Texas examined the change in number of crashes ( 18 ); however, documentation of speed of turning vehicles before and after such an improvement was not reported. A study in Peoria, Illinois ( 19 ) included the observation of driver behavior along with evaluating the change in crashes caused by modifications of the right-turn approaches. Field observations of driver behavior at the right-turn lanes at 10 test sites and 10 control sites were collected.…”
Section: Review Of Literaturementioning
confidence: 99%